Compound
Patent Information
- Application Number
- JP2023211787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-21
- Filing Date
- 2023-12-15
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-02-19
AI Technical Summary
【0012】 本発明の液晶配向剤を用いることで、液晶配向性やその他の特性を低下することなく、液晶配向膜の機械的強度を向上させた液晶配向膜を得ることができる。
Smart Images

Figure 0007652237000001 
Figure 0007652237000002 
Figure 0007652237000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystal aligning agent used in the production of a liquid crystal display element, a liquid crystal alignment film obtained from the liquid crystal aligning agent, and a liquid crystal display element using the liquid crystal alignment film. [Background technology]
[0002] Liquid crystal display elements are known as display devices that are lightweight, thin, and consume little power. Liquid crystal display elements are constructed by sandwiching a liquid crystal layer between a pair of transparent substrates equipped with electrodes. In liquid crystal display elements, an organic film made of an organic material is used as a liquid crystal alignment film so that the liquid crystal is aligned in a desired state between the substrates. In recent years, high display quality is required for high-definition liquid crystal display elements for smartphones and tablet terminals, and liquid crystal alignment films are also required to have a variety of high-level properties in addition to liquid crystal alignment ability.
[0003] In order to meet these requirements, a method of adding low molecular weight compounds having various properties to a liquid crystal alignment agent for producing a liquid crystal alignment film has been widely used. For example, in order to improve the mechanical strength of the resulting liquid crystal alignment film, a liquid crystal alignment agent containing a low molecular weight compound that improves the hardness of the liquid crystal alignment film has been proposed (see Patent Documents 1 and 2). This low molecular weight compound contains a group that undergoes a crosslinking reaction during a heating step performed in the liquid crystal alignment film production process, and polymers are linked together by crosslinking, thereby improving the mechanical strength of the resulting liquid crystal alignment film. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-544185 A [Patent Document 2] Patent No. 617911 Summary of the Invention [Problem to be solved by the invention]
[0005] However, a common problem with the above method is the deterioration of liquid crystal alignment. The three-dimensional cross-linking of the polymer in the liquid crystal alignment film prevents the liquid crystal from aligning in a certain direction. In addition, the presence of unreacted low molecular weight compounds can also have a negative effect on the liquid crystal alignment.
[0006] A main object of the present invention is to provide a liquid crystal aligning agent capable of improving the mechanical strength of a liquid crystal alignment film without deteriorating the liquid crystal alignment property and other properties. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the gist of the present invention is as follows. 1. A liquid crystal aligning agent comprising the following components (A) and (B), and an organic solvent:
[0008] Component (A): at least one polymer selected from the group consisting of polyimide precursors and imidized polymers of the polyimide precursors.
[0009] Component (B): a compound having a group having a hydroxyalkylamide group and a structure represented by the following formula (1):
[0010] [ka]
[0011] R1 to R4 each independently represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and * represents a bond to another atom. Effect of the Invention
[0012] By using the liquid crystal aligning agent of the present invention, it is possible to obtain a liquid crystal alignment film having improved mechanical strength without deteriorating the liquid crystal alignment property and other properties.
[0013] It is not entirely clear why the present invention provides the above-mentioned effects, but it is generally believed to be for the following reason.
[0014] The compound of component (B) contained in the liquid crystal alignment agent of the present invention has a polyimide skeleton structure as shown in formula (1). Since the compound has a structure similar to the polymer of component (A) in this way, it is considered that the liquid crystal is not hindered from being aligned along the polymer. In addition, in the liquid crystal alignment film obtained by the process of aligning the liquid crystal by irradiating polarized ultraviolet light, the cyclobutane structure in formula (1) is decomposed by the irradiation of polarized ultraviolet light, so it is considered that the alignment of the liquid crystal is not hindered. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] <Component (A)> The component (A) contained in the liquid crystal aligning agent of the present invention is at least one polymer selected from the group consisting of polyimide precursors and imidized polymers of the polyimide precursors, and its structure is not particularly limited.
[0016] <Tetracarboxylic acid derivatives> The polyimide precursor contained in the liquid crystal aligning agent of the present invention is obtained by reacting a tetracarboxylic acid derivative with a diamine, and the polyimide is obtained by imidizing the polyimide precursor. Specific examples of the materials used and the production method are described in detail below.
[0017] Examples of the tetracarboxylic acid derivatives used in the production of the polyimide precursor include not only tetracarboxylic acid dianhydrides but also their derivatives, such as tetracarboxylic acids, tetracarboxylic acid dihalide compounds, tetracarboxylic acid dialkyl esters, and tetracarboxylic acid dialkyl ester dihalides.
[0018] Of the tetracarboxylic dianhydrides and derivatives thereof, those represented by the following formula (2) are preferred.
[0019] [ka]
[0020] In formula (2), the structure of X1 is not particularly limited. Preferred specific examples include the following formulae (X1-1) to (X1-44).
[0021] [ka]
[0022] [ka]
[0023] [ka]
[0024] [ka]
[0025] [ka]
[0026] [ka]
[0027] In formulae (X1-1) to (X1-4), R 11 ~R 31 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group. 23 is preferably a hydrogen atom, a halogen atom, a methyl group, or an ethyl group, and more preferably a hydrogen atom or a methyl group.
[0028] Specific examples of formula (X1-1) include the following formulae (X1-1-1) to (X1-1-6): (X1-1-1) is particularly preferred from the standpoint of liquid crystal alignment properties and photoreaction sensitivity.
[0029] [ka]
[0030] <Diamine> The diamine used in the production of the polyimide precursor is represented by the following formula (3).
[0031] [ka]
[0032] In the above formula (3), A1 and A2 each independently represent a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an alkynyl group having 2 to 5 carbon atoms.
[0033] The structure of Y1 is not particularly limited. Preferred structures include the following (Y-1) to (Y-182).
[0034] [ka]
[0035] [ka]
[0036] [ka]
[0037] [ka]
[0038] [ka]
[0039]
change
[0040]
change
[0041]
change
[0042]
change
[0043]
change
[0044]
change
[0045]
change
[0046]
change
[0047]
change
[0048]
change
[0049] [ka]
[0050] [ka]
[0051] [ka]
[0052] [ka]
[0053] [ka]
[0054] In the above formula, Me represents a methyl group, R 1 represents a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms.
[0055] [ka]
[0056] Among them, the structure of Y1 is (Y-7), (Y-8), (Y-16), (Y-17), (Y-18), (Y-20), (Y-21), (Y-22), (Y-28), (Y-35), (Y-38), (Y-43), (Y-48), (Y-64), (Y- 66), (Y-71), (Y-72), (Y-76), (Y-77), (Y-80), (Y-81), (Y-82), (Y-83), (Y-156), (Y-159), (Y-160), (Y-161), (Y-162)(Y-168), (Y-169), (Y-170), (Y-171), (Y-173), and (Y-175) are preferred, particularly (Y-7), (Y-8), (Y-16), (Y-17), (Y-18), (Y-21), (Y-22), (Y-28), (Y-38), (Y-64), and (Y-66). , (Y-72), (Y-76), (Y-81), (Y-156), (Y-159), (Y-160), (Y-161), (Y-162), (Y-168), (Y-169), (Y-170), (Y-171), (Y-173), and (Y-175) are preferred.
[0057] <(B) component> The component (B) contained in the liquid crystal aligning agent of the present invention is a compound having a group having a hydroxyalkylamide group and a structure of the following formula (1).
[0058] [ka]
[0059] R1 to R4 each independently represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. A hydrogen atom or a methyl group is preferable. * represents a bond to another atom.
[0060] The component (B) preferably has two or more hydroxyalkylamide groups. The structure of the group having two or more hydroxyalkylamide groups is not particularly limited, but from the viewpoint of availability, a preferred example is a compound represented by the following formula (4).
[0061] [ka]
[0062] X2 is an (n+1)-valent organic group containing an aliphatic hydrocarbon group having 1 to 20 carbon atoms or an aromatic hydrocarbon group, n is an integer of 2 to 6, and * represents a bond to (1).
[0063] R5 and R6 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms which may have a substituent, an alkenyl group having 2 to 4 carbon atoms which may have a substituent, or an alkynyl group having 2 to 4 carbon atoms which may have a substituent. At least one of R5 and R6 represents a hydrocarbon group substituted with a hydroxyl group.
[0064] In the formula (4), n is preferably 2 to 4 from the viewpoint of solubility.
[0065] In formula (4), at least one of R5 and R6 is preferably a structure represented by the following formula (5) from the viewpoint of reactivity, and more preferably a structure represented by the following formula (6).
[0066] [ka]
[0067] In formula (5), R7~R 10 are each independently a hydrogen atom, a hydrocarbon group, or a hydrocarbon group substituted with a hydroxyl group.
[0068] [ka]
[0069] Specific preferred examples of the component (B) include the following compounds.
[0070] [ka]
[0071] If the amount of component (B) is too large, it affects the liquid crystal alignment property and the pretilt angle, whereas if the amount is too small, the effects of the present invention cannot be obtained. Therefore, the content of component (B) is preferably 3 to 30 mass %, more preferably 5 to 15 mass %, of component (A).
[0072] <Polyamic acid> The polyamic acid, which is a polyimide precursor used in the present invention, can be produced by the following method. Specifically, it can be synthesized by reacting a tetracarboxylic dianhydride with a diamine in the presence of an organic solvent at -20°C to 150°C, preferably 0°C to 50°C, for 30 minutes to 24 hours, preferably 1 to 12 hours.
[0073] The organic solvent used in the above reaction is preferably N,N-dimethylformamide, N-methyl-2-pyrrolidone, or γ-butyrolactone in terms of the solubility of the monomer and polymer, and these may be used alone or in combination of two or more. The concentration of the polymer is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the viewpoints that the polymer is less likely to precipitate and a high molecular weight product is easily obtained.
[0074] The polyamic acid obtained as described above can be recovered by injecting the reaction solution into a poor solvent while thoroughly stirring it to precipitate the polymer. In addition, the precipitation can be carried out several times, washed with a poor solvent, and then dried at room temperature or by heating to obtain a purified polyamic acid powder. The poor solvent is not particularly limited, but examples thereof include water, methanol, ethanol, hexane, butyl cellosolve, acetone, and toluene.
[0075] <Polyamic acid ester> The polyamic acid ester, which is one of the polyimide precursors used in the present invention, can be produced by the following method (1), (2) or (3).
[0076] (1) Manufacturing from polyamic acid The polyamic acid ester can be synthesized by esterifying a polyamic acid obtained from a tetracarboxylic dianhydride and a diamine, specifically by reacting a polyamic acid with an esterifying agent in the presence of an organic solvent at −20° C. to 150° C., preferably 0° C. to 50° C., for 30 minutes to 24 hours, preferably 1 to 4 hours.
[0077] The esterification agent is preferably one that can be easily removed by purification, and examples of the esterification agent include N,N-dimethylformamide dimethyl acetal, N,N-dimethylformamide diethyl acetal, N,N-dimethylformamide dipropyl acetal, N,N-dimethylformamide dineopentyl butyl acetal, N,N-dimethylformamide di-t-butyl acetal, 1-methyl-3-p-tolyltriazene, 1-ethyl-3-p-tolyltriazene, 1-propyl-3-p-tolyltriazene, 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride, etc. The amount of the esterification agent used is preferably 2 to 6 molar equivalents per mole of the repeating unit of the polyamic acid.
[0078] The solvent used in the above reaction is preferably N,N-dimethylformamide, N-methyl-2-pyrrolidone, or γ-butyrolactone in terms of the solubility of the polymer, and these may be used alone or in combination of two or more. The concentration of the polymer in the reaction solution is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the viewpoints that the polymer is unlikely to precipitate and a high molecular weight product is easily obtained.
[0079] (2) When produced by reacting a tetracarboxylic acid diester dichloride with a diamine The polyamic acid ester can be produced from a tetracarboxylic acid diester dichloride and a diamine. Specifically, the polyamic acid ester can be synthesized by reacting the tetracarboxylic acid diester dichloride and the diamine in the presence of a base and an organic solvent at −20° C. to 150° C., preferably 0° C. to 50° C., for 30 minutes to 24 hours, preferably 1 to 4 hours.
[0080] The base may be pyridine, triethylamine, 4-dimethylaminopyridine, etc., but pyridine is preferred because the reaction proceeds mildly. The amount of the base used is preferably 2 to 4 times the molar amount of the tetracarboxylic acid diester dichloride, from the viewpoints of easy removal and easy production of a high molecular weight compound.
[0081] The solvent used in the above reaction is preferably N-methyl-2-pyrrolidone or γ-butyrolactone in terms of the solubility of the monomer and polymer, and these may be used alone or in combination of two or more. The polymer concentration in the reaction solution is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the viewpoint of preventing precipitation of the polymer and facilitating the production of a high molecular weight polymer. In addition, in order to prevent hydrolysis of the tetracarboxylic acid diester dichloride, it is preferable that the solvent used in the synthesis of the polyamic acid ester is as dehydrated as possible, and it is preferable to use a nitrogen atmosphere to prevent the inclusion of outside air.
[0082] (3) Production by reacting a tetracarboxylic acid diester with a diamine The polyamic acid ester can be produced by polycondensing a tetracarboxylic acid diester and a diamine, specifically, by reacting a tetracarboxylic acid diester and a diamine in the presence of a condensing agent, a base, and an organic solvent at 0° C. to 150° C., preferably 0° C. to 100° C., for 30 minutes to 24 hours, preferably 3 to 15 hours.
[0083] The condensing agent may be triphenyl phosphite, dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-carbonyldiimidazole, dimethoxy-1,3,5-triazinylmethylmorpholinium, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, (2,3-dihydro-2-thioxo-3-benzoxazolyl)diphenylphosphonate, etc. The amount of the condensing agent added is preferably 2 to 3 times the molar amount of the tetracarboxylic acid diester.
[0084] The base may be a tertiary amine such as pyridine, triethylamine, etc. The amount of the base used is preferably 2 to 4 times the molar amount of the diamine component, from the viewpoints of easy removal and easy production of a high molecular weight substance.
[0085] In the above reaction, the reaction can be efficiently carried out by adding a Lewis acid as an additive. The Lewis acid is preferably a lithium halide such as lithium chloride or lithium bromide. The amount of Lewis acid added is preferably 0 to 1.0 times the molar amount of the diamine component.
[0086] Among the above three methods for producing a polyamic acid ester, the above method (1) or the above method (2) is particularly preferred since it gives a high molecular weight polyamic acid ester.
[0087] The polyamic acid ester solution obtained as described above can be poured into a poor solvent while being thoroughly stirred to precipitate the polymer. Precipitation can be carried out several times, washed with a poor solvent, and then dried at room temperature or by heating to obtain a purified polyamic acid ester powder. The poor solvent is not particularly limited, but examples thereof include water, methanol, ethanol, hexane, butyl cellosolve, acetone, and toluene.
[0088] <Polyimide> The polyimide used in the present invention can be produced by imidizing the polyamic acid or polyamic acid ester. The imidization rate of the polyimide used in the present invention is not limited to 100%. From the viewpoint of electrical properties, it is preferably 20 to 99%. When producing a polyimide from a polyamic acid ester, chemical imidization is simple, in which a basic catalyst is added to the polyamic acid ester solution or a polyamic acid solution obtained by dissolving a polyamic acid ester resin powder in an organic solvent. Chemical imidization is preferable because the imidization reaction proceeds at a relatively low temperature and the molecular weight of the polymer is less likely to decrease during the imidization process.
[0089] Chemical imidization can be carried out by stirring the polyamic acid or polyamic acid ester to be imidized in an organic solvent in the presence of a basic catalyst and an acid anhydride. In addition, by reacting the compounds shown in the following (R-1) to (R-2) at that time, a polyimide precursor having a specific structure introduced at the end can be obtained. The organic solvent can be the solvent used in the polymerization reaction described above. Examples of the basic catalyst include pyridine, triethylamine, trimethylamine, tributylamine, and trioctylamine. Among them, pyridine is preferable because it has a suitable basicity for promoting the reaction. Examples of the acid anhydride include acetic anhydride, trimellitic anhydride, and pyromellitic anhydride, and among them, the use of acetic anhydride is preferable because it makes purification after the reaction easy. Usually, in the case of conventional polyimides, when acetic anhydride is used, an acetyl group is generated as the main chain end, whereas the present invention can suppress acetylation.
[0090] [ka]
[0091] R 22 , R 22' represents a monovalent organic group, specific examples of which include a methyl group, an ethyl group, a propyl group, a 2,2,2-trichloroethyl group, a 2-trimethylsilylethyl group, a 1,1-dimethylpropynyl group, a 1-methyl-1-phenylethyl group, a 1-methyl-1-(4-biphenylyl)ethyl group, a 1,1-dimethyl-2-haloethyl group, a 1,1-dimethyl-2-cyanoethyl group, a tert-butyl group, a cyclobutyl group, a 1-methylcyclobutyl group, a 1-adamantyl group, a vinyl group, an allyl group, a cinnamyl group, an 8-quinolyl group, an N-hydroxypiperidinyl group, a benzyl group, a p-nitrobenzyl group, a 3,4-dimethoxy-6-nitrobenzyl group, a 2,4-dichlorobenzyl group, and a 9-fluorenylmethyl group.
[0092] The temperature when carrying out the imidization reaction is, for example, -20°C to 120°C, preferably 0°C to 100°C, and the reaction time can be 1 to 100 hours. The amount of the basic catalyst is 0.5 to 30 times by mole, preferably 2 to 20 times by mole, the amic acid group, and the amount of the acid anhydride is 1 to 50 times by mole, preferably 3 to 30 times by mole, the amic acid group. The imidization rate of the obtained polymer can be controlled by adjusting the amount of the catalyst, the temperature, and the reaction time.
[0093] Since the added catalyst and the like remain in the solution after the imidization reaction of the polyamic acid ester or polyamic acid, it is preferable to recover the obtained imidized polymer by the means described below and re-dissolve it in an organic solvent to obtain the liquid crystal aligning agent of the present invention.
[0094] The polyimide solution obtained as described above can be poured into a poor solvent while being thoroughly stirred to precipitate the polymer. The precipitation is carried out several times, washed with a poor solvent, and then dried at room temperature or by heating to obtain a purified powder of polyamic acid ester.
[0095] The poor solvent is not particularly limited, but examples thereof include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, and benzene.
[0096] <Liquid crystal alignment agent> The liquid crystal alignment agent used in the present invention has the form of a solution in which at least one polymer selected from the group consisting of polyimide precursors and imidized polymers of the polyimide precursors (hereinafter referred to as a polymer having a specific structure), which is the component (A), and a compound having a hydroxyalkylamide group, which is the component (B), are dissolved in a solvent.
[0097] The molecular weight of the specific structure polymer is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and even more preferably 10,000 to 100,000, and the number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and even more preferably 5,000 to 50,000.
[0098] The concentration of the polymer in the liquid crystal aligning agent of the present invention can be appropriately changed depending on the thickness of the coating film to be formed, but from the viewpoint of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the viewpoint of storage stability of the solution, it is preferably 10% by mass or less, and particularly preferably 3 to 6.5% by mass.
[0099] The solvent (also called a good solvent) contained in the liquid crystal aligning agent of the present invention is not particularly limited as long as the specific structure polymer can be uniformly dissolved therein.
[0100] Examples of the solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethylsulfoxide, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, and 4-hydroxy-4-methyl-2-pentanone.
[0101] Of these, it is preferable to use N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, or γ-butyrolactone.
[0102] Furthermore, when the polymer of the present invention has high solubility in a solvent, it is preferable to use a solvent represented by the following formulas [D-1] to [D-3]. [ka] (D 1 ~D 3 represents an alkyl group having 1 to 6 carbon atoms.
[0103] The good solvent in the liquid crystal aligning agent of the present invention is preferably 20 to 99% by mass of the entire solvent contained in the liquid crystal aligning agent, more preferably 20 to 90% by mass, and more preferably 30 to 80% by mass.
[0104] The liquid crystal aligning agent of the present invention can use a solvent (also called a poor solvent) that improves the coating property and surface smoothness of the liquid crystal alignment film when the liquid crystal aligning agent is applied, as long as the effect of the present invention is not impaired. Specific examples of poor solvents are listed below, but are not limited to these examples.
[0105] For example, ethanol, isopropyl alcohol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentyl alcohol, tert-pentyl alcohol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, ethanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane, ethylene Glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, ethylene glycol monoethyl ether, noacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol,Dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol mono Examples of the solvent include methyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, and the solvents represented by the formulas [D-1] to [D-3].
[0106] Of these, it is preferable to use 1-hexanol, cyclohexanol, 1,2-ethanediol, 1,2-propanediol, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, or dipropylene glycol dimethyl ether.
[0107] The poor solvent preferably accounts for 1 to 80% by mass, more preferably 10 to 80% by mass, and even more preferably 20 to 70% by mass of the entire solvent contained in the liquid crystal aligning agent.
[0108] In addition to the above, the liquid crystal aligning agent of the present invention may contain, within a range that does not impair the effects of the present invention, a polymer other than the polymer described in the present invention, a dielectric or conductive substance for the purpose of changing the electrical properties such as the dielectric constant or conductivity of the liquid crystal alignment film, a silane coupling agent for the purpose of improving the adhesion between the liquid crystal alignment film and the substrate, a crosslinking compound for the purpose of increasing the hardness or denseness of the film when made into a liquid crystal alignment film, and an imidization accelerator for the purpose of efficiently proceeding with imidization by heating the polyimide precursor when baking the coating film.
[0109] <Liquid crystal alignment film> <Method of manufacturing liquid crystal alignment film> The liquid crystal alignment film of the present invention is a film obtained by applying the liquid crystal alignment agent to a substrate, drying and baking the same. The substrate to which the liquid crystal alignment agent of the present invention is applied is not particularly limited as long as it is a highly transparent substrate, and glass substrates, silicon nitride substrates, acrylic substrates, polycarbonate substrates and other plastic substrates can be used. Furthermore, from the viewpoint of simplifying the process, it is preferable to use a substrate on which an ITO electrode or the like for driving liquid crystal is formed. In addition, in a reflective liquid crystal display element, an opaque material such as a silicon wafer can be used for only one substrate, and in this case, a light-reflecting material such as aluminum can be used for the electrode.
[0110] Examples of the method for applying the liquid crystal alignment agent of the present invention include spin coating, printing, and inkjet methods. The drying and baking process after applying the liquid crystal alignment agent of the present invention can be performed at any temperature and time. In general, in order to sufficiently remove the solvent contained, the coating is dried at 50 to 120°C, preferably 60 to 100°C, for 1 to 10 minutes, preferably 2 to 5 minutes, and then baked at 150 to 300°C, preferably 200 to 240°C, for 5 to 120 minutes, preferably 10 to 30 minutes. The thickness of the coating film after baking is not particularly limited, but is 5 to 300 nm, preferably 10 to 200 nm, since if it is too thin, the reliability of the liquid crystal display element may decrease.
[0111] The method for performing alignment treatment on the obtained liquid crystal alignment film includes a rubbing method, a photo-alignment method, and the like.
[0112] The rubbing treatment can be carried out using an existing rubbing device. Examples of the material for the rubbing cloth include cotton, nylon, and rayon. The conditions for the rubbing treatment are generally a rotation speed of 300 to 2000 rpm, a feed speed of 5 to 100 mm / s, and a pressing depth of 0.1 to 1.0 mm. After that, the residues generated by rubbing are removed by ultrasonic cleaning using pure water or alcohol.
[0113] A specific example of the photo-alignment treatment method is a method in which the coating surface is irradiated with radiation polarized in a certain direction, and in some cases, further heat-treated at a temperature of 150 to 250°C to impart liquid crystal alignment ability. As the radiation, ultraviolet rays and visible light having a wavelength of 100 to 800 nm can be used. Among these, ultraviolet rays having a wavelength of 100 to 400 nm are preferred, and ultraviolet rays having a wavelength of 200 to 400 nm are particularly preferred. In order to improve the liquid crystal alignment property, the coating substrate may be irradiated with radiation while being heated at 50 to 250°C. The radiation dose is 1 to 10,000 mJ / cm. 2 is preferable, and 100 to 5,000 mJ / cm 2 The liquid crystal alignment film prepared as described above can stably align liquid crystal molecules in a certain direction.
[0114] The higher the extinction ratio of the polarized UV light, the higher the anisotropy that can be imparted, which is preferable. Specifically, the extinction ratio of linearly polarized UV light is preferably 10:1 or more, and more preferably 20:1 or more.
[0115] The film irradiated with polarized radiation as described above may then be contact-treated with a solvent containing at least one selected from the group consisting of water and organic solvents.
[0116] The solvent used in the contact treatment is not particularly limited as long as it dissolves the decomposition product generated by light irradiation. Specific examples include water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, and cyclohexyl acetate. Two or more of these solvents may be used in combination.
[0117] From the viewpoint of versatility and safety, at least one selected from the group consisting of water, 2-propanol, 1-methoxy-2-propanol, and ethyl lactate is more preferable. Water, 2-propanol, or a mixed solvent of water and 2-propanol is particularly preferable.
[0118] In the present invention, the contact treatment between the film irradiated with polarized radiation and the solution containing a solvent is preferably carried out by a method such as immersion treatment or spraying treatment, which allows sufficient contact between the film and the solution. Among these, a method of immersion treatment in a solution containing a solvent for preferably 10 seconds to 1 hour, more preferably 1 to 30 minutes, is preferred. The contact treatment may be carried out at room temperature or heated, and is preferably carried out at 10 to 80°C, more preferably 20 to 50°C. Furthermore, a means for enhancing contact, such as ultrasonic waves, may be applied as necessary.
[0119] After the contact treatment, in order to remove the solvent in the solution used, either rinsing with a low boiling point solvent such as water, methanol, ethanol, 2-propanol, acetone, or methyl ethyl ketone and / or drying may be performed.
[0120] Furthermore, the membrane that has been contacted with a solution containing a solvent may be heated at 150° C. or higher for the purposes of drying the solvent and reorienting the molecular chains in the membrane.
[0121] The heating temperature is preferably 150 to 300° C. The higher the temperature, the more the reorientation of the molecular chains is promoted, but if the temperature is too high, there is a risk of decomposition of the molecular chains. Therefore, the heating temperature is more preferably 180 to 250° C., and particularly preferably 200 to 230° C.
[0122] If the heating time is too short, the effect of reorienting the molecular chains may not be obtained, whereas if it is too long, the molecular chains may decompose. Therefore, the heating time is preferably 10 seconds to 30 minutes, and more preferably 1 to 10 minutes.
[0123] <Liquid crystal display element> The liquid crystal display element of the present invention is characterized by comprising a liquid crystal alignment film obtained by the above-mentioned method for producing a liquid crystal alignment film.
[0124] The liquid crystal display element of the present invention is obtained by obtaining a substrate with a liquid crystal alignment film from the liquid crystal alignment agent of the present invention by the method for producing a liquid crystal alignment film, and then producing a liquid crystal cell by a known method, and using the liquid crystal cell as a liquid crystal display element.
[0125] As an example of a method for fabricating a liquid crystal cell, a passive matrix liquid crystal display element will be described below. However, an active matrix liquid crystal display element in which switching elements such as TFTs (Thin Film Transistors) are provided in each pixel portion constituting an image display may also be used.
[0126] First, transparent glass substrates are prepared, and a common electrode is provided on one substrate, and a segment electrode is provided on the other substrate. These electrodes may be, for example, ITO electrodes, and are patterned so as to display a desired image. Next, an insulating film is provided on each substrate so as to cover the common electrode and the segment electrode. The insulating film may be, for example, a film made of SiO2-TiO2 formed by the sol-gel method.
[0127] Next, the liquid crystal alignment film of the present invention is formed on each substrate. Next, one substrate is superimposed on the other substrate so that the alignment film surfaces face each other, and the periphery is bonded with a sealant. Spacers are usually mixed into the sealant in order to control the gap between the substrates. It is also preferable to disperse spacers for controlling the gap between the substrates even in the in-plane portion where no sealant is provided. An opening is provided in a part of the sealant so that liquid crystal can be filled from the outside.
[0128] Next, liquid crystal material is injected into the space surrounded by the two substrates and the sealant through an opening in the sealant. This opening is then sealed with an adhesive. The injection may be performed using a vacuum injection method or a method utilizing capillary action in the atmosphere. Next, polarizing plates are installed. Specifically, a pair of polarizing plates are attached to the surfaces of the two substrates opposite the liquid crystal layer. Through the above steps, the liquid crystal display element of the present invention is obtained.
[0129] In the present invention, the sealing agent is, for example, a resin having a reactive group such as an epoxy group, an acryloyl group, a (meth)acryloyl group, a hydroxyl group, an allyl group, an acetyl group, etc., which is cured by ultraviolet irradiation or heating. In particular, it is preferable to use a curable resin system having both reactive groups, an epoxy group and a (meth)acryloyl group.
[0130] The sealing agent of the present invention may contain an inorganic filler for the purpose of improving adhesion and moisture resistance. The inorganic filler that can be used is not particularly limited, but specifically includes spherical silica, fused silica, crystalline silica, titanium oxide, titanium black, silicon carbide, silicon nitride, boron nitride, calcium carbonate, magnesium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, alumina, magnesium oxide, zirconium oxide, aluminum hydroxide, calcium silicate, aluminum silicate, lithium aluminum silicate, zirconium silicate, barium titanate, glass fiber, carbon fiber, molybdenum disulfide, asbestos, etc. Preferred are spherical silica, fused silica, crystalline silica, titanium oxide, titanium black, silicon nitride, boron nitride, calcium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, alumina, aluminum hydroxide, calcium silicate, or aluminum silicate. The inorganic fillers may be used in a mixture of two or more kinds. EXAMPLES
[0131] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the following, the abbreviations of compounds and the measuring methods of each property are as follows. NMP: N-methyl-2-pyrrolidone GBL: γ-butyl lactone BCS: Butyl cellosolve THF: tetrahydrofuran DMF: N,N-dimethylformamide
[0132] [ka]
[0133] [ka]
[0134] [ka]
[0135] < 1 HNMR measurement> Equipment: Fourier transform superconducting nuclear magnetic resonance spectrometer (FT-NMR) "AVANCE 3" (BRUKER) 500MHz. Solvent: deuterated chloroform (CDCl3) or deuterated N,N-dimethylsulfoxide ([D6]-DMSO). Standard substance: tetramethylsilane (TMS).
[0136] [viscosity] The viscosity of the polyimide and polyamic acid solutions was measured using an E-type viscometer (VE-22H, manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL, a cone rotor TE-1 (1°34′, R24), and a temperature of 25°C.
[0137] [Measurement of imidization rate] 20 mg of polyimide powder was placed in an NMR sample tube (Kusano Scientific NMR Sampling Tube Standard φ5), 0.53 ml of deuterated dimethyl sulfoxide (DMSO-d6, 0.05% TMS (tetramethylsilane) mixture) was added, and ultrasonic waves were applied to completely dissolve the powder. This solution was measured by 500 MHz proton NMR using a JEOL Datum NMR analyzer (JNW-ECA500). The imidization rate was calculated by the following formula using the proton peak integrated value of this proton and the proton peak integrated value of the proton peak derived from the NH group of the amic acid that appears around 9.5 to 10.0 ppm.
[0138] Imidization rate (%) = (1-α·x / y) × 100
[0139] [Preparation of liquid crystal cells] A liquid crystal cell having the structure of an FFS mode liquid crystal display element was fabricated. First, a substrate with electrodes was prepared. The substrate was a rectangular glass plate measuring 30 mm x 50 mm and 0.7 mm thick. An ITO electrode with a solid pattern was formed on the substrate as the first layer, which constituted the counter electrode. A SiN (silicon nitride) film formed by CVD was formed on the first layer of the counter electrode as the second layer. The thickness of the second layer of the SiN film was 500 nm, and it functions as an interlayer insulating film. A comb-shaped pixel electrode formed by patterning the ITO film as the third layer was arranged on the second layer of the SiN film, forming two pixels, a first pixel and a second pixel. The size of each pixel was 10 mm long and about 5 mm wide. At this time, the first layer of the counter electrode and the third layer of the pixel electrode were electrically insulated by the action of the second layer of the SiN film.
[0140] The pixel electrode in the third layer has a comb-like shape composed of multiple electrode elements arranged in a "L" shape with a bent central portion. The width of each electrode element in the short direction is 3 μm, and the distance between the electrode elements is 6 μm. Since the pixel electrode forming each pixel is composed of multiple electrode elements arranged in a "L" shape with a bent central portion, the shape of each pixel is not rectangular, but has a shape similar to a bold "L" shape that is bent in the center like the electrode elements. Each pixel is divided into upper and lower parts by the central bend, and has a first region above the bent part and a second region below the bent part.
[0141] Comparing the first and second regions of each pixel, the directions of the electrode elements of the pixel electrodes that compose them are different. That is, based on the rubbing direction of the liquid crystal alignment film described later, the electrode elements of the pixel electrodes in the first region of the pixel are formed to form an angle of +10° (clockwise), and the electrode elements of the pixel electrodes in the second region of the pixel are formed to form an angle of -10° (clockwise). That is, the first and second regions of each pixel are configured such that the directions of the rotational movement (in-plane switching) of the liquid crystal in the substrate plane induced by the application of a voltage between the pixel electrode and the counter electrode are opposite to each other.
[0142] Next, the obtained liquid crystal alignment agent was filtered through a filter with a pore size of 1.0 μm, and then spin-coated onto the above-prepared electrode-attached substrate and a glass substrate having a 4 μm-high columnar spacer with an ITO film formed on the back side. After drying for 2 minutes on a hot plate at 80°C, it was baked for 30 minutes at 230°C in an IR oven to form a coating film with a thickness of 100 nm. Polarized ultraviolet light was irradiated onto the coating surface at 300 mJ / cm. 2 The substrate was irradiated with light so that the alignment was performed. The substrate was baked again at 230°C for 30 minutes using an IR oven to obtain a substrate with a liquid crystal alignment film. The above two substrates were combined into a set, a sealant was printed on the substrate, and another substrate was attached so that the alignment direction of the liquid crystal alignment film faces each other was 0°, and then the sealant was cured to produce an empty cell. Liquid crystal MLC-3019 (manufactured by Merck) was injected into this empty cell by a reduced pressure injection method, and the injection port was sealed to obtain an FFS drive liquid crystal cell. The obtained liquid crystal cell was then heated at 110°C for 1 hour and left overnight before being used for image retention evaluation.
[0143] Since AD-3 and AD-4 are new compounds with no literature registration, synthesis examples are described below. (Synthesis Example 1: Synthesis of AD-3) [ka]
[0144] 4-Aminophenylacetic acid (10.6 g, 70 mmol), DAH-1 (7.5 g, 33.6 mmol), and acetic acid (120 g) were charged into a 500 mL four-neck flask and stirred under reflux. After the reaction was completed, the reaction solution was poured into pure water (800 g) and the precipitate was filtered off. THF (120 g) was added to the obtained crude product, which was then repulped and washed at room temperature to obtain 32.6 g of [AD-3-1]. [AD-3-1] (30.0 g, 61 mmol), bis[2-(trimethylsilyloxy)ethyl]amine (45.8 g, 184 mmol), (2,3-dihydro-2-thioxo-3-benzoxazolyl)diphenylphosphonate (47.0 g, 122 mmol), triethylamine (45.8 g, 184 mmol), and NMP (450 g) were charged into a 2 L four-neck flask and stirred at room temperature. After the reaction was completed, the reaction solution was poured into a 0.5 mol / L aqueous hydrochloric acid solution (2500 g), and the precipitate was filtered off. Methanol (300 g) was added to the obtained crude product, which was then repulped and washed at room temperature to obtain 30.3 g of [AD-3] (white solid). 1 The results of H-NMR are shown below, and it was confirmed that the obtained solid was the desired [AD-3]. 1 H NMR (500 MHz, [D6]-DMSO):δ7.32-7.38 (m,8H), 4.92-4.95 (t,2H), 4.69-4.72 (t,2H), 3.82 (s,4H), 3.55-3.59 (m,6H), 3.47-3.52 (m,8H), 3.36-3.39 (m,4H), 1.40 (s,6H)
[0145] (Synthesis Example 2: Synthesis of AD-4) [ka]
[0146] 4-Aminobenzoic acid (32.9 g, 24 mmol), DAH-1 (26.9 g, 12 mmol), and AcOH (540 g) were charged into a 2 L four-neck flask and stirred under reflux. After the reaction was completed, the reaction solution was poured into pure water (3500 g) and the precipitate was filtered off. Methanol (1200 g) was added to the obtained crude product, which was then repulped and washed at room temperature to obtain 40.4 g of [AD-4-1].
[0147] [AD-4-1] (40.4 g, 87 mmol), bis[2-(trimethylsilyloxy)ethyl]amine (76.0 g, 305 mmol), (2,3-dihydro-2-thioxo-3-benzoxazolyl)diphenylphosphonate (83.7 g, 218 mmol), triethylamine (30.9 g, 305 mmol), and NMP (400 g) were charged into a 1 L four-neck flask and stirred at room temperature. After the reaction was completed, the reaction solution was poured into methanol (600 g) and the precipitate was filtered off. Methanol (500 g) was added to the obtained crude product, trifluoroacetic acid (7 g) was added to make it acidic, and the precipitate was filtered off. Furthermore, DMF (400 g) was added to the crude product and completely dissolved at 50 ° C., and the insoluble matter was filtered off. The obtained filtrate was poured into ethyl acetate (2500 g), and the precipitate was filtered off and dried to obtain 48.8 g of [AD-4] (white solid). 1 The results of H-NMR are shown below, and it was confirmed that the obtained solid was the desired [AD-4]. 1 H NMR (500 MHz, [D6]-DMSO):δ7.56-7.58 (d,4H), 7.48-7.50 (d,4H), 4.84-4.87 (t,4H), 3.61-3.65 (m,6H), 3.55-3.56 (d,4H), 3.48-3.50 (d,4H), 3.35 (s,4H), 1.42 (s,6H)
[0148] (Production Example 1) DA-1 (1.08g, 10mmol), DA-2 (3.66g, 15mmol), DA-3 (4.81g, 15mmol), and DA-4 (3.41g, 10mmol) were added to a 200ml four-neck flask equipped with a stirrer and nitrogen inlet tube, and then 132g of NMP was added and dissolved by stirring while supplying nitrogen. DAH-1 (10.54g, 47mmol) was added to this diamine solution while stirring, and 40.3g of NMP was added. The mixture was further stirred at 40°C for 12 hours to obtain a polyamic acid solution (PAA-1) with a resin solids concentration of 12% by mass. The viscosity of this polyamic acid solution at 25°C was 380mPa·s.
[0149] 60.0 g of the obtained polyamic acid solution (PAA-1) was dispensed into a 200 ml Erlenmeyer flask, 20.0 g of NMP was added thereto, followed by 4.56 g of acetic anhydride and 1.18 g of pyridine, and the mixture was reacted at 55°C for 3 hours. The reaction solution was poured into 300 g of methanol, and the resulting precipitate was filtered off. The precipitate was washed with methanol and dried under reduced pressure at 80°C to obtain polyimide powder. The imidization rate of this polyimide was 66%. 26.4 g of NMP was added to 3.6 g of the obtained polyimide powder, and the mixture was stirred at 70°C for 20 hours to dissolve the mixture, obtaining a polyimide solution (SPI-1).
[0150] (Production Example 2) 3.99g (20mmol) of DA-5 and 1.49g (5mmol) of DA-6 were weighed into a 100mL four-neck flask equipped with a stirrer and a nitrogen inlet tube, then 78g of NMP was added and dissolved by stirring while supplying nitrogen. 6.77g (23mmol) of DAH-2 was added while stirring this diamine solution, and NMP was further added so that the solid concentration became 12% by mass. The mixture was stirred at 70℃ for 20 hours to obtain a polyamic acid solution (PAA-2) (viscosity: 420mPa s).
[0151] Comparative Example 1 5.63 g of the polyimide solution (SPI-1) obtained in Production Example 1 was weighed out into a 50 mL Erlenmeyer flask containing a stirrer. 3.34 g of NMP, 2.03 g of GBL, 3.00 g of BCS, and 1.01 g of a 10% NMP solution of AD-1 were added, and the mixture was stirred overnight with a magnetic stirrer to obtain a liquid crystal alignment agent (AL-1).
[0152] Comparative Example 2 5.63 g of the polyimide solution (SPI-1) obtained in Production Example 1 was weighed out into a 50 mL Erlenmeyer flask containing a stirrer. 3.34 g of NMP, 2.03 g of GBL, 3.00 g of BCS, and 1.01 g of a 10% NMP solution of AD-2 were added, and the mixture was stirred overnight with a magnetic stirrer to obtain a liquid crystal alignment agent (AL-2).
[0153] Example 1 5.63 g of the polyimide solution (SPI-1) obtained in Production Example 1 was weighed out into a 50 mL Erlenmeyer flask containing a stirrer. 3.34 g of NMP, 2.03 g of GBL, 3.00 g of BCS, and 1.01 g of a 10% NMP solution of AD-3 were added, and the mixture was stirred overnight with a magnetic stirrer to obtain a liquid crystal alignment agent (AL-3).
[0154] Example 2 5.63 g of the polyimide solution (SPI-1) obtained in Production Example 1 was weighed out into a 50 mL Erlenmeyer flask containing a stirrer. 3.34 g of NMP, 2.03 g of GBL, 3.00 g of BCS, and 1.01 g of a 10% NMP solution of AD-4 were added, and the mixture was stirred overnight with a magnetic stirrer to obtain a liquid crystal alignment agent (AL-4).
[0155] Example 3 In a 50 mL Erlenmeyer flask containing a stirrer, 1.13 g of the polyimide solution (SPI-1) obtained in Production Example 1 was weighed out, and 4.50 g of the polyamic acid solution (PAA-2) obtained in Production Example 2 was added. Furthermore, 0.86 g of NMP, 4.50 g of GBL, 3.00 g of BCS, and 1.01 g of a 10% NMP solution of AD-3 were added, and the mixture was stirred overnight with a magnetic stirrer to obtain a liquid crystal alignment agent (AL-5).
[0156] [Evaluation of image lag due to long-term AC drive] Using the above liquid crystal cell, an AC voltage of ±5 V at a frequency of 30 Hz was applied for 120 hours in a constant temperature environment of 60° C. After that, the pixel electrode and the counter electrode of the liquid crystal cell were shorted, and the liquid crystal cell was left at room temperature for one day.
[0157] After leaving it, the liquid crystal cell was placed between two polarizing plates arranged so that the polarization axes were perpendicular to each other, and the backlight was turned on with no voltage applied, and the arrangement angle of the liquid crystal cell was adjusted so that the brightness of the transmitted light was minimized. Then, the rotation angle when the liquid crystal cell was rotated from the angle at which the second region of the first pixel was the darkest to the angle at which the first region was the darkest was calculated as the angle Δ. Similarly, the second region and the first region of the second pixel were compared, and the same angle Δ was calculated. Then, the average value of the angle Δ values of the first pixel and the second pixel was calculated as the angle Δ of the liquid crystal cell. The liquid crystal cell obtained above was evaluated as "x" when the angle Δ was 0.15° or more, and as "good" when it was less than 0.15°.
[0158] (Comparative Examples 3 and 4, Examples 4, 5, and 6) The liquid crystal alignment agents (AL-1, AL-2, AL-3, AL-4, AL-5) obtained were subjected to long-term AC drive image retention evaluation as described above. That is, liquid crystal cells having the configuration of FFS mode liquid crystal display elements were prepared as described above using the liquid crystal alignment agents (AL-1, AL-2, AL-3, AL-4, AL-5), and the FFS drive liquid crystal cells were subjected to long-term AC drive image retention evaluation. The results are summarized in Table 1 below.
[0159] [Table 1]
[0160] [Membrane strength evaluation] The liquid crystal alignment agent was applied by spin coating to the ITO surface of a glass substrate with an ITO electrode on the entire surface. After drying for 2 minutes on a hot plate at 80°C, it was baked for 30 minutes at 230°C in an IR oven to form a coating film with a thickness of 100 nm. Polarized ultraviolet light was applied to the coating surface at 300 mJ / cm. 2The substrate was irradiated with light so that the alignment treatment was performed. The substrate was baked again in an IR oven at 230°C for 30 minutes to obtain a substrate with a liquid crystal alignment film. This liquid crystal alignment film was rubbed with a rayon cloth (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, indentation length: 0.6 mm). The substrate was observed under a microscope, and was evaluated as "good" if no streaks were observed on the film surface due to rubbing, and "poor" if streaks were observed.
[0161] (Comparative Examples 5 and 6, Examples 7, 8, and 9) The obtained liquid crystal alignment agents (AL-1, AL-2, AL-3, AL-4, and AL-5) were subjected to the above-mentioned film strength evaluation. The results are summarized in Table 2 below.
[0162] [Table 2]
[0163] The above results are summarized in Table 3 below.
[0164] [Table 3]
[0165] As shown in Table 3, the liquid crystal alignment agents using AD-3 and AD-4, which have both an imide ring skeleton and an alkylamide skeleton, were able to achieve both good alignment and high rubbing resistance.
Claims
[Claim 1] Any of the following compounds: 【Chemistry 1】
Citation Information
Patent Citations
Power source turning-on and-off circuit
JP1986007911A
Composition for liquid crystal orienting film, liquid crystal orienting film, liquid crystal holding substrate and liquid crystal display device
JP1998078586A
Composition for liquid crystal alignment film, liquid crystal alignment film, liquid crystal holding substrate and liquid crystal display element
JP2001510497A
JP2010-544185A
Liquid crystal aligning agent and liquid crystal display device
JP2010244015A